Se parece com Nelson é vida ou A Psicanálise como ela é...: narrativas de uma investigação psicanalítica - Costa, Rafael de Melo (2013)
This text is an investigative study that, under the interpretative lens of psychoanalysis method, puts in question the concepts of psychoanalytic interpretation and psychic reality, which is made from an analogy established between the creation movements in Nelson Rodrigues Literature and those from the psychoanalytic productions. The reading of A vida como ela é..., series of tales written by Nelson Rodrigues to Última Hora newspaper, between 1951 and 1961, turned out to be a strong theoretical and affective experience. When he produces, Nelson creates realities and a particular form of man the Brazilian. He presents tragedies and dramas, to which, untangles the ululant obvious which sustain them. In this sense, I deducted that he would fulfill, with methodological rigour, the interpretative method demands by disrupting the course, as proposed by Fabio Herrman, which means the creation of a meaning that goes beyond the established routinely. Shocked by the possibility of a writer/artist fulfilling the demands of the psychoanalytic method, I presumed if Nelson Rodrigues was not an exemplary psychoanalyst. In the face of this agony and the position taken to see/read Nelson Rodrigues production as psychoanalytic, I needed dialogues with Science, Arts, in a deeper way with Literature, to illuminate the field and place of Psychoanalysis in my universe, and answer the nodal points which were imposed to the investigation: what Nelson Rodrigues produces of knowledge about the human condition can be equivalent to the knowledge coming from the psychoanalytic lens?; what is the difference between the analytical process and the creative writers process, considering the fictional character which unfold from them?; and Would Nelson Rodrigues be a psychoanalyst to be followed on the basis of his creation way and the disruption promoted by his action? More than an exercise of theoretical construction, this investigation, organized in narratives which store the seal of processed search way, which is, questioner and interpretative or as I call investicrativa, brings the movement of particular reinvention to Psychoanalysis. Looking to the keyhole, I encountered the character of mistake and uncertainness which constitutes life and also the psychoanalytic art. Facing the uncertain, it was necessary to be tragic and artist to dare a draft of my invention as a psychoanalyst and, from this place, produce a man and reality, in the transferencial dialogue with Nelson Rodrigues in A Carta, in the theories articulated in O Texto, or yet, in the appropriation of a clinical case through the tale A Deprimida, path which made it possible for me the suspension and expression of desire. In this way, two points are apprehended in this investigation, which ratify the analogy between Psychoanalysis and Literature, as suggested in Theory of the analogous, once both create meanings, not real, but possibilities of meanings, and the place that writing assumes in both fields.